Dietary energy levels alter production performance, egg quality, and intestinal health of Wenshui green-shell layers in the peak laying period - Liu, Wenjing; Di, Yanjiao; Lu, Qikun; Jiang, Yu; Yuan, Xuejun; Jiang, Shuzhen; Yang, Weiren; Jiao, Ning (Frontiers in Veterinary Science, 2025)
IntroductionThe Wenshui green-shell layers is a new layer breed, and the appropriate metabolizable energy (ME) have not been identified as the lack of breed-specific feeding standards. Therefore, this study aimed to investigate the effects of dietary energy levels on production performance, egg quality and intestinal health of Wenshui green-shell layers to identify appropriate ME in the peak laying period.MethodsA total of 600 33-week-old Wenshui green-shell layers were selected and randomly assigned to five treatment groups, with eight replicates of 15 laying hens each. The hens were fed with diets with ME level of 2,400 (ME2400), 2,500 (ME2500), 2,600 (ME2600), 2,700 (ME2700) and 2,800 (ME2800) kcal/kg for 42 days.Results and discussionThe results showed that the production performance of layers showed a quadratic curvilinear change with ME levels increase, and the ME2700 group obtained the optimal production performance and dry matter apparent availability. The serum albumin and triglyceride contents were linearly increased with the ME levels increase, while serum total antioxidant capacity of the ME2700 group was significantly higher than that in other groups. Additionally, egg quality was showed the quadratic curvilinear improvement, while the nutrient contents in eggs and superoxide dismutase activity in egg albumen were increased with increasing ME levels. Besides, the ME2700 group had a better morphology in oviduct and small intestine. Energy levels regulated the intestinal microbiota composition, notably ME2700 increased the relative abundance of Rikenellaceae_RC9_gut_group. On the other hand, the abundance of Bacteroides was negatively correlated with egg and albumen weight, while that of Fusobacterium was positively correlated with egg yolk ratio. In conclusion, the appropriate dietary ME level was 2,700 kcal/kg, which could improve production performance, egg quality and intestinal health in Wenshui green-shell layers during peak laying period.